Sistematika Kongkang Jeram Huia masonii (Boulenger, 1884) Berdasarkan Karakter Morfologi - Haekal, Muhammad; Hamidy, Amir; Yudha, Donan Satria; Eprilurahman, Rury (Bioma : Berkala Ilmiah Biologi, 2020)
Huia masonii (Boulenger, 1884) or Javan Torrent Frog is one of the frogs that are endemic on the island of Java. The presumption of two different forms of Huia's morphology according to Manthey and Dezer’s publication makes a systematic study of these species among their populations necessary. In this study, a systematic study of H.masonii was conducted between populations with a morphological approach to determine differences in character between populations, taxonomic status and phylogeny between populations. A total of 111 adult specimens (62 males and 49 females) from each population with good condition were observed morphologically. Data analysis was performed using Principal Component Analysis (PCA) and UPGMA Clustering. The results of this study indicate that there are no fundamental differences in the characteristics of each population so that there are no characters that can be used as diagnostic characters. The absence of this diagnostic character also makes the taxonomic status of H. masonii morphologically unchanged. Besides relationship between populations is still close to one another morphologically